Chondrogenesis of Human Infrapatellar Fat Pad Stem Cells on Acellular Dermal Matrix - Ye, Ken; Traianedes, Kathy; Choong, Peter F. M.; Myers, Damian E. (Frontiers in Surgery, 2016)
Acellular dermal matrix (ADM) has been in clinical use for decades in numerous surgical applications. The ability for ADM to promote cellular repopulation and revascularisation, and tissue regeneration is well documented. Adipose stem cells have the ability to differentiate into mesenchymal tissue types, including bone and cartilage. The aim of this study was to investigate the potential interaction between ADM and adipose stem cells in vitro using TGFβ3 and BMP6. Human infrapatellar fat pad derived adipose stem cells (IPFP-ASC) were cultured with ADM derived from rat dermis under chondrogenic (TGFβ3 and BMP6) in vitro for 2 and 4 weeks. Histology, qPCR and immunohistochemistry were performed to assess for markers of chondrogenesis (collagen Type II, SOX9 and proteoglycans). At 4 weeks, cell-scaffold constructs displayed cellular changes consistent with chondrogenesis, with evidence of stratification of cell layers and development of a hyaline-like cartilage layer superficially which stained positively for collagen Type II and proteoglycans. Significant cell-matrix interaction was seen between the cartilage layer and the ADM itself with seamless integration between each layer. Real time qPCR showed significantly increases of COL2A1, SOX9, and ACAN gene expression over 4 weeks when compared to control. COL1A2 gene expression remained unchanged over 4 weeks. We believe the principles which make ADM versatile and successful for tissue regeneration are application to cartilage regeneration. This study demonstrates in vitro the ability for IPFP-ASCs to undergo chondrogenesis, infiltrate and interact with ADM. These outcomes serve as a platform for in vivo modelling of ADM for cartilage repair.